Analisis Penerapan Electronic Registration (E-Reg) (Studi Kasus Pada Kpp Purwokerto Jawa Tengah) - Icuk Rangga Bawono; Budiman Prayudi; Dendra Kurnianto; Andi Sucito (Politeknik Negeri Lampung, 2008)
Income tax represents one of the direct taxes collected by government from taxpayer. With the existence of fiscal self assessment, taxpayer can calculate, payi and report the amount of owned debt tax according to Law at a particular period of tax, part of tax year, or a tax year. This means taxpayer is responsible to that tax obligation. Each taxpayer should have fundamental number of taxpayer or NPWP as taxpayer identity in executing obligation of their tax. With the existence of information technology and in order to improve service to taxpayers obliged to conducive tax, they might register themselves and report their business activity through the information system network which in circuit on-line. This system called with Electronic Registration is operated by internet. Taxpayer needn't come again to office to enlist. This Electronic Registration has been provided only for personal taxpayer. With the existence of system of Electronic Registration this of taxpayer candidate given by amenity in course of registration of them self become taxpayer. This research analyzed the amount of personal taxpayer enlist before and after the existence of Electronic Registration. Keywords: Electronic Registration, pajak, wajib pajak